LEGAL PROTECTION FOR COMPOSERS OF SONGS THAT HAVE NOT BEEN REGISTERED WITH THE DIRECTORATE-GENERAL OF INTELLECTUAL PROPERTY - ANTON SUJATMIKO (LOIS: Jurnal Hukum dan Humaniora, 2026)
This research aims to uphold copyright protection, as copyright represents the creative works of individuals or groups and recognizes their achievements through legal recognition. It is expected that creators will be protected under Law Number 28 of 2014, particularly Article 40 paragraph (3), which regulates the protection of works that have not been published or announced but have been realized in tangible form. However, this provision still creates ambiguity, especially regarding copyrights that have not been formally registered. This research employs a normative juridical method with a legislative approach. The findings demonstrate that the concept of legal protection for song copyrights that remain unregistered with the Directorate General of Intellectual Property Rights (DJKI) but have already been published to the public still requires greater legal certainty. The author investigated relevant legal regulations and laws to explain the legal consequences for song creators whose works contain elements of similarity or have been plagiarized by third parties. While Law Number 28 of 2014 establishes a framework for copyright protection, there is currently no legal certainty guaranteeing protection for works that have not been registered with copyright authorities. This is because the concept of exclusive rights as inherent and natural rights provides the meaning that such rights serve as a guarantee for every creator to obtain legal protection.